Altered Brain Activation in Early Drug-Naive Parkinson’s Disease during Heat Pain Stimuli: An fMRI Study - Ying Tan; Juan Tan; Cheng Luo; Wenjuan Cui; Hui He; Yi Bin; Jiayan Deng; Rui Tan; Wenrong Tan; Tao Liu; Nanlin Zeng; Ruhui Xiao; et al. (Parkinson's Disease)
Parkinson’s disease (PD) is a progressive neurodegenerative disease characterized by motor and nonmotor signs and symptoms. To date, many studies of PD have focused on its cardinal motor symptoms. To study the nonmotor signs of early PD, we investigated the reactions solicited by heat pain stimuli in early untreated PD patients without pain using fMRI. The activation patterns of contact heat stimuli (51°C) were assessed in 14 patients and 17 age- and sex-matched healthy controls. Patients with PD showed significant decreases in activation of the superior temporal gyrus (STG) and insula compared with controls. In addition, a significant relationship between activation of the insula and STG and the pain scores was observed in healthy controls but not in PD. This study provided further support that the insula and STG are important parts of the somatosensory circuitry recruited during the period of pain. The hypoactivity of the STG and insula in PD implied that functions including affective, cognitive, and sensory-discriminative processes, which are associated with the insula and STG, were disturbed. This finding supports the view that leaving early PD untreated could be tied directly to central nervous system dysfunction.